If Germany Came to New Zealand - Salmond, John (Victoria University of Wellington Law Review, 1999)
This article is a report from the New Zealand Mail, 1 August 1906, which covered Professor John Salmond’s inaugural address as the chair of law at Victoria College (now Victoria University of Wellington). Professor Salmond dealt with the subject of international law with regards to the conditions of modern warfare. He discusses important international treaties, the role of the civil population, and what would happen if war came to New Zealand. Professor Salmond concludes that a key player in resolving international disputes was arbitration, which he believed was full of hope and promise for the future.